P161 Paediatric analgesia: prescribing patterns and challenges facing surgical NCHDs in a non-specialist paediatric hospital. (June 2019) - O'Sullivan, Mai; Dolan, Anne
Abstract : Introduction: Acute pain is one of the most common adverse stimuli experienced by children, often recurring pre and post-operatively. It is associated with increased anxiety, somatic symptoms, avoidance and increased parental distress 1 . Effective treatment is essential to prevent long term psychological changes 2 . An Acute Pain Service (APS) was established in Sligo University Hospital in January 2019 to meet the growing demands of our peri-operative inpatient population. At this time, little was known about the current local practices of our surgical colleagues when prescribing simple analgesia for children. Aims: This study aimed to investigate the prescribing patterns and challenges faced by Surgical Non-Consultant Hospital Doctors (NCHDs) when prescribing for children. Methods: A paper-based survey was conducted in January 2019. It was sent to all General Surgical, Orthopaedic and Ear Nose and Throat NCHDs. It contained 24 questions. They related to teaching received in paediatric prescribing, familiarity with pain assessment tools used to quantify children's pain, including the FACES score and the sources of information currently used to calculate doses. We asked specifically about prescribing for children in the obese and underweight categories. Confidence levels prescribing analgesia for children was assessed using a Likert Scale. The involvement of parents and nursing staff in the management of pain by surgical NCHDs was also assessed. Results: The paper-based survey was administered to 32 NCHDs. Experience level ranged from Intern to Specialist Registrar. The response rate was 68%. The majority of respondents did not feel confident prescribing analgesia for children. The BNF for children was the most common source used for dosing calculations. 12% selected the correct method for prescribing analgesia for the obese and underweight child. There was poor involvement of parents and nursing staff in analgesia planning and engagement in distraction techniques. Conclusion: Surgical NCHDs in our institution are uncomfortable prescribing simple analgesia for children. They are open to, and would likely benefit from receiving educational sessions on this topic from the APS. Further guidance will be offered to surgical NCHDs in our institution going forward, particularly in relation to children who are at extremes of weight. References: American Academy of Paediatrics, American Pain Society. The Assessment and Management of Acute Pain in Infants, Children and Adolescents. Paediatrics 2001; 108(3):793–797. Kulshrestha, A. and Bajwa, S. (2019). Management of acute postoperative pain in pediatric patients. Anaesthesia, Pain & Intensive Care, 22, 3(1607–8322), pp.2220–5799.